Waste to energy: the effects of Pseudomonas sp. on Chlorella sorokiniana biomass and lipid productions in palm oil mill effluent - Cheah, Wai Yan; Show, Pau Loke; Juan, Joon Ching; Chang, Jo-Shu; Ling, Tau Chuan (Springer, 2018)
Microalgae are recognised as promising feedstock for biofuel production. The feasibility in commercial scale microalgae cultivation could be enhanced by incorporating palm oil mill effluent (POME) as culture medium, for greater biomass growth and lipid production, together with POME bioremediation. The polluting POME is generated massively in Malaysia. POME contains high concentrations of carbon and nutrients, thus it is suitable to be applied for microalgae cultivation. The approach on waste to energy should be advanced. We studied the effects of applying Pseudomonas sp. on Chlorella sorokiniana CY-1 cultivation in POME. Pseudomonas sp. was found effective in POME decolourisation prior to C. sorokiniana CY-1 cultivation. Yet, microalgae biomass and lipid productions were higher in the non-decolourised POME. Pseudomonas sp. was as well-being co-cultivated with C. sorokiniana CY-1 in ratios of microalgae versus bacteria of 1:1; 2:1 and 1:2. Biomass of 2.04 g L−1 and biomass productivity of 185.71 mg L−1 d−1 were attained in ratio of 1:1. Interestingly, the lipid content exhibited was excellent (16.04%), and about twofold higher than other ratios and the control (without bacteria). Fatty acids compositions were dominated by C16:0 (32.49%), C18:1 (24.06%) and C18:2 (20.28%), which were desirable fatty acids for biodiesel production. Effective POME bioremediation achieved with chemical oxygen demand, total nitrogen and total phosphorus removal of 53.7, 55.6 and 77.3%, respectively. Co-cultivation of microalgae and bacteria can be applied in the POME treatment plant. This allows satisfactory biomass and excellent lipid yields for biofuel production, as well as effective wastewater bioremediation.